The Use of Beta-Blockers in Hereditary Hemorrhagic Telangiectasia-Related Epistaxis: A Systematic Review. Issue 6 (November 2022) - Albarki, Hashm; Rimmer, Joanne
Background: Hereditary hemorrhagic telangiectasia (HHT) is an autosomal dominant disease affecting 1 in 5000 individuals. Epistaxis is seen in more than 90% of patients with HHT. Severe recurrent epistaxis can significantly decrease quality of life and may be resistant to standard treatment measures. Dysregulation of angiogenesis has been shown to cause the proliferation of abnormal blood vessels. As such, antiangiogenic treatments have been investigated including beta-blockers. Objective: A systematic review of the efficacy of beta-blockers in topical treatment of epistaxis in patients with HHT based on epistaxis duration, frequency, and severity. Methods: A systematic search was performed using the PubMed, Embase via Ovid, and Cochrane databases. The Preferred Items for Systematic Reviews and Meta-Analyses guidelines were followed. Studies that measured the efficacy of beta-blocker treatment of epistaxis in patients with HHT were included for qualitative analysis. Results: Five studies (3 randomized controlled trials and 2 case series) with a total of 132 patients were included. Administration (systemically or topically via a spray or gel) of timolol and propranolol showed mixed evidence of improvement in epistaxis frequency, severity, and duration when compared with control groups. The evidence for propranolol appears more promising than timolol. Conclusion: There are significant limitations in the included studies, and further investigation with larger longitudinal or randomized prospective trials is recommended. The available evidence suggests that beta-blocker treatment may have a positive effect on HHT-related epistaxis.